In vivo detection of drug-induced apoptosis in tumors using Raman spectroscopy. Issue 20 (2nd August 2018) - Jonas, Oliver; Kang, Jeon Woong; Singh, Surya P.; Lammers, Alex; Nguyen, Freddy T.; Dasari, Ramachandra R.; So, Peter T. C.; Langer, Robert; Cima, Michael J.
Abstract : We describe a label-free approach based on Raman spectroscopy, to study drug-induced apoptosis in vivo . Abstract : We describe a label-free approach based on Raman spectroscopy, to study drug-induced apoptosis in vivo . Spectral-shifts at wavenumbers associated with DNA, proteins, lipids, and collagen have been identified on breast and melanoma tumor tissues. These findings may enable a new analytical method for rapid readout of drug-therapy with miniaturized probes.